Régimen de licencias obligatorias y uso público no comercial en Argentina - Juan Ignacio Correa Amunátegui (South Centre, 2024)
– With the adoption of the Agreement on Trade-Related Aspects of Intellectual Property Rights (TRIPS), Argentina had to adapt to the new international rules on patent law. One of the main points of the Agreement is the possibility of establishing different forms of compulsory licenses and governmental non-commercial use. This paper analyzes the conditions foreseen in article 31 of the TRIPS Agreement for that purpose and examines in detail the different grounds for compulsory licenses contemplated in the Argentine legislation and the conditions applicable to each of them, as well as for the use of patents by the government for non-commercial purposes. Finally, based on the normative scope of TRIPS and the current legislation, the paper discusses the possible content of a compulsory licensing and public non-commercial use regulation that would allow Argentina to effectively use these tools when any of the circumstances foreseen in the current regulation arise.
Keywords: 300; Patent law; legal harmonization; TRIPS; Argentina; Patentrecht; Rechtsangleichung; TRIPS; Argentinien